A paisagem na região leste de Roraima, município de Bonfim: aspectos fisiográficos, morfológicos, granulométricos e mineralógicos dos ambientes lacustres - Alves, Raquel Araújo (2016)
The district of Bonfim located northeast of the state of Roraima is characterized in that sequences of mountains, hills, ravines hills and hills with deep valleys, as well as residual elevations that stand out in a large flat surface, in addition to the formation of sandy soils and high precipitation index contribute to the occurrence of lacustrine environment. This study proposed to analyze the landscape through the geomorphological aspects to understand the lacustrine environment in the urban expansion area of the city of Bonfim. Therefore, it was necessary literature, mapping and remote sensing, field activities in order to identify and describe the compartments and geomorphological units. Analysis of morphological, granulometrics, mineralogical and chemical point of soil / lake sediments were also held. The results showed that the landscape of Bonfim region is represented by modeled dissecting represented by: Landings in Structured Crista, Massif Somite Convex, Residual Hills Structured, Hills and Hills Staggerd to Opened Valleys and Opened Dissected Hills, linked to Erosive Plains, Plain Surface and Alluvial Plain along the drainages. The lacustrine environments, significant features in this landscape, occur with predominantly circular and oval morphology and elongated in lower proportion, compounds and dendritic. A lot of them has intermittent regimen example, the Italian Lake in contrast to the perennial system represented by the Bicho Lake. They are densely colonized by aquatic weeds such as sedges which are distributed according to variations of these depths. The sediments / soils are predominantly sandy, with angular grains sub angular. They are composed mainly of quartz and kaolinite secondarily, and goethite and muscovite. The chemical composition highlights high concentrations of SiO2, Fe2O3 and Al2O3, stating the minerals found in these sediments. The lacustrine environments have been subjected to intense anthropic pressure, represented by the disorderly occupation which led to problems such as releases of domestic sewage and solid waste disposal. Therefore, it is necessary attention to the processes that occur in these environments because they contribute to understanding the dynamics of the transformation of the landscape especially when combined with urban sprawl.